RETENTION STAGE BEFORE FINAL PROTHETICS OF DISABLED CHILDREN WITH UNILATERAL CLEFT LIP AND PALATE - A. F. Verapatvelian; S. S. Gushina (Кубанский научный медицинский вестник, 2016)
Result evaluation of complex treatment is very important at the final stage of rehabilitation of the 17-24-year-old patient with a unilateral cleft lip and palate (UCLP). During this period, it can be relatively easy to assess the defects and mistakes of treatment at previous stages, and to fix themif it is possible. Possibility of occlusion correction increases after a thorough analysis of the previous stages of complex rehabilitation of disabled children with UCLP. This increases the doctor motivation to medical history survey of the child and to a more accurate registration of objective data. This creates optimal conditions for the planning of further orthodontic and orthopedic treatment and comparing the results to the moment of rational prosthetics.